Experimental and numerical study on the effect of CO2 dilution on the laminar combustion characteristics of premixed CH4/H2/air flame. (June 2022) - Chen, Jianing; Chen, Guoyan; Zhang, Anchao; Deng, Haoxin; Wen, Xiaoping; Wang, Fahui; Mei, Yanyang
Abstract: The effects of diluents on the characteristics of constant volume combustion and Chemkin-Pro laminar premixed combustion were investigated. The laminar combustion characteristics of the CH4 /H2 /CO2 /N2 mixtures under different initial conditions were studied by using a chemical kinetic model. After experiment and comparison, the FFCM-1 mechanism works well. Based on the laminar burning velocity (LBV), a numerical decoupling method was used to separate the three effects of diluent CO2 : the dilution effect, the thermal effect and the chemical effect, those show that three effects increased with the rising initial temperature while the elevated pressure reversed. The unit fuel, thermal parameters and active free radicals were gained by parameter analysis, sensitivity analysis, chemical path analysis and mole fraction analysis, which increased the LBV and caused the three effects to change. The R32 takes the leading role with initial temperature increased and the R54 and R84 play a key role in the chemical effect in rising initial pressure, respectively. The effect of CO2 on the combustion characteristics of CH4 /H2 mixture was investigated under this work, which provided a theoretical reference for exhaust gas recirculation. Highlights: The effect of dilution gas on LBV of CH4 /H2 syngas was analysed. Numerical decoupling analyzes the three effects of diluent gas on CH4 /H2 syngas. A detailed sensitivity analysis and a kinetic analysis were performed. Reaction(R32), (R54) and (R84) are the dominant factor in chemical effect of CO2 .